The Role of Ethnopedagogy in Instilling Character Through Traditional Games in Elementary School Students' Physical Education Subjects - Rama Zidan Primaniar; Achmad Nuryadi (Universitas Sriwijaya in Collaboration with HDPGSDI (Himpunan Dosen PGSD Indonesia), 2026)
Elementary school students' character education needs to be developed through contextual and meaningful Physical Education learning by integrating local cultural values, through an ethnopedagogical approach based on traditional games. This study aims to examine the role of ethnopedagogy in instilling students' character values ​​through the implementation of traditional games. The study used a qualitative approach with a case study method. Data collection techniques were carried out through observation, interviews, and documentation. The results showed that traditional game-based Physical Education learning was able to increase student activity, enthusiasm, and involvement in the learning process. Traditional games were also effective in internalizing character values, such as honesty, discipline, responsibility, cooperation, empathy, and tolerance. Teachers considered that traditional games were more effective and efficient than modern games because they were easy to implement, did not require many facilities, and were appropriate to the characteristics of elementary school students. This study concluded that the integration of ethnopedagogy in Physical Education learning played an important role in creating active, contextual, and meaningful learning, preserving local culture, and building character.